ANALYSIS OF FACTORS OF NURSE COMPLIANCE IN THE APPLICATION OF STANDARD PRECAUTION TO THE PREVENTION OF COVID-19 - Muhammad, Safrullah; Muliana, Nyanyak (Jurnal Keperawatan Respati Yogyakarta, 2022)
Corona Virus Disease 2019 (COVID-19) has spread around the world resulting in a very rapid increase in morbidity and can lead to death. Since the beginning of 2020 there has been an increase in the number of cases of COVID-19 virus infection. The ratio of deaths and exposure to COVID-19 for nursing personnel in Indonesia is among the highest compared to other countries. Therefore, efforts are needed to make "Medical Safety and Protection" namely with the application of Standard Precaution. This study aims to find out what factors affect nurse compliance in the implementation of Standard Precaution to prevent COVID-19 transmission. This type of research is correlative quantitative research with a cross-sectional approach. The population in this study was the nurse of the emergency room and the men's internal medicine room Tgk Abdullah Syafi'i Hospital. The sampling technique in this study is a total sampling with the number of nurses as many as 87people. The results of the study were analyzed univariately and bivariately using Spearman rank statistics and multivariate analysis with logistic regression tests. The results showed that 86.3% of nurses adhered to the implementation of standard precaution in preventing the transmission of Covid-19 Tgk Abdullah Syafi'i Hospital. from the results of bivariate analysis shows there is a significant relationship between Attitude (p value = 0.007), barrier to application of standard precaution (p value = 0.005), Availabilityanmeans infection prevention facility (p value = 0.000) against the application of standardd precaution. The results of multivariate analysis showed that Availabilityan meansof infection prevention facilities is the most dominant factor in the prevention of covid-19 transmission with an OR value of 12. 936. The conclusion is that there is a meaningful relationship between the application of standard transmission of covid-19 in nurses. It is expected to the hospital to pay full attention to the availabilityof infection prevention facilities in emergency departments and internal medicine rooms. Keywords: Standard Precaution; Nurse; Compliance; Covid-19